PENGARUH PENDIDIKAN, TINGKAT UPAH DAN PENGANGGURAN TERHADAP PERSENTASE PENDUDUK MISKIN DI KABUPATEN/KOTA PROVINSI BALI - Cok Istri, Dian Purnama Yanti; A A I N, Marhaeni (PIRAMIDA; Vol 11 No 2 (2015): JURNAL PIRAMIDA, 2015)
One of the objectives of national development is to improve the performance of the economy in order to create jobs and organize a decent life for all the people who in turn will realize the welfare of the population. One of the main indicators of the success of national development is the rate of decrease in the number of poor people. The purpose of this study was to determine: 1) direct influence between education, wages, and unemployment to the percentage of the poor; 2) the influence of education and the level of wages indirectly to the percentage of poor people through unemployment in the district / city of Bali province. This study uses secondary data analysis Path Analysis. The results showed showed that the negative effect of education on unemployment and wages positive effect on unemployment. Education and wage levels negatively affect the percentage of poor and unemployed positive effect on the percentage of poor people. In addition there is an indirect effect of education and wage levels on the percentage of poor people through unemployment, in other words, unemployment is mediating variables in the influence of education and the level of wages on the percentage of poor people in the district / city of Bali province.
Keywords: education; wages; unemployment; percentage of poor